Pharmaceutical science: new insights and developments Vol. 8 - Ghannam, Wagih Mommtaz (editor) (BP International, 2025)
This book covers key areas of pharmaceutical science. The contributions by the authors include herbal cream, Biophytum sensitivum, antibacterial activity, Chronotherapy, chrono-pharmaceutics, pharmacodynamics, equivalent dose modelling, dose justification, liver enzymes, sarkaraikolli, glibenclamide, gestational diabetes mellitus, Nyaope, substance abuse, recreational drug, liver damage, drug utilisation review, emergency department, Mimosa pudica, phytotherapeutic, intestinal infections, medicinal plants, breath analysis, volatile organic compounds, fourier transform infrared spectroscopy, non-volatile compounds. This book contains various materials suitable for students, researchers, and academicians in the fields of pharmaceutical science.
Book
Keywords: Pharmaceutical science; Drugs -- Research; Pharmaceutical industry